Correlation between Myeloperoxidase and Interleukin-6 of Patients with Obstructive Sleep Apnea Syndrome in Thi-Qar Governorate - Albadri, Mahdi Maid Yousif; Husam M. Kredy,; Majeed Mohan ALhamami, (University of Thi-Qar Journal of Science, 2024)
AbstractThis research aimed to detect the relationship between Myeloperoxidase (MPO) and Interleukin-6 (IL-6) in patients obstructive sleep apnea syndrome (OSAS). The present study has been conducted on a number of healthy people and patients. Group A: 84 patients Obstructive sleep apnea syndrome (mild, mod and sever) with high blood pressure [47 male, 37 female] and age range (40 - 65). Group B: control group, consist of 64 healthy people [33 male, 31 female] and age range (40 - 65). The findings from the current research indicated a notable rise in levels of serum MPO and serum IL-6 among patient groups when compared with the control group (P≤0.05). Results indicated that there was a positive correlation between MPO with IL-6 in patients with OSAS. OSA patients show high serum myeloperoxidase and serum interleukin-6 concentrations, which signal heightened systemic inflammation and oxidative stress. These factors, part of the pathogenesis of cardiovascular disease are important risk predictors to measure in OSA patients: this can be helpful for early diagnosis of the disease.